Evaluation of a Drug Testing and Graduated Sanctions Program in Delaware, 2010-2012 - O'Connell, Daniel ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The "Design Your Time" (DYT) program was designed to test, in a real world setting, the efficacy of systematically providing increased monitoring of probationers coupled with known, certain and quickly enforced sanctions to reduce substance use and increase positive probationer outcomes. Developed from a model of deterrence, the program informed eligible probationers of what exactly was required of them, what would happen to them when they failed to meet requirements (increased sanctions), and how to reduce their level of monitoring once they violated and triggered increased sanctions (reduced sanctions and garnered rewards). The program utilized a model based on deterrence in which certainty and speed, rather than immediate severity, were the key elements. It also empowered the probationer by clearly informing him or her of the elements of the program, thus allowing them to "Decide Your Time." The program focused on those offenders who tested positive for drugs at intake and involved frequent urinalysis for offenders, coupled with increasing sanctions and referral to treatment. The collection includes 1 SPSS data file with 404 variables and 400 cases. Data from qualitative interviews with probationers, day to day observations in the probation office, qualitative interviews with the DYT probation officers conducted three months after that program launched, and a focus group with the DYT officers at the conclusion of the study are not available.